A DNA‐Encoded Chemical Library Based on Peptide Macrocycles. Issue 24 (18th March 2021) - Onda, Yuichi; Bassi, Gabriele; Elsayed, Abdullah; Ulrich, Franziska; Oehler, Sebastian; Plais, Louise; Scheuermann, Jörg; Neri, Dario
Abstract: The synthesis and characterization of a novel DNA‐encoded library of macrocyclic peptide derivatives are described; the macrocycles are based on three sets of proteinogenic and non‐proteinogenic amino acid building blocks and featuring the use of copper(I)‐catalyzed alkyne‐azide cycloaddition (CuAAC) reaction for ring closure. The library (termed YO‐DEL) which contains 1 254 838 compounds, was encoded with DNA in single‐stranded format and was screened against target proteins of interest using affinity capture procedures and photocrosslinking. YO‐DEL selections yielded specific binders against serum albumins, carbonic anhydrases and NKp46, a marker of activated Natural Killer cells. Abstract : A DNA‐encoded chemical library (DEL) based on canonical and non‐canonical peptide macrocycles (YO‐DEL) was generated. The single‐stranded format allowed for selections by affinity capture, through a novel selection method exploiting the competition with an antibody fragment and the annealing to a photoreactive moiety which allowed for selections by a photocrosslinking approach. The YO‐DEL yielded ligands against proteins of pharmaceutical interest such as CAIX, HSA and NKp46, a protein expressed on the surface of activated NK‐cells.